The Home Security Monitoring System with Passive Infrared Receiver, Temperature Sensor and Flame Detector Based on Android System - Uman Putra, Novian Patria; Firdaus, Aji Akbar; Winarno, Winarno; Prasaja, Alim; Setiawati, Kadek Juni (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2021)
A home state monitoring is important for homeowners. Because in Indonesia, theft and fire are common occurrences. This is caused by the negligence of homeowners. Therefore, home security monitoring systems are made to minimize theft and house fires. In this study, home security monitoring systems were made using human motion detection sensors or PIR (Passive Infrared Receiver) sensors, temperature sensors, flame detectors, buzzers, and pumps. The PIR sensor is used to detect thieves so buzzer can sound. The Temperature sensor and flame detector are used to detect fires then the pump will extinguish the fire. The system is then integrated with android HP devices, so homeowners can monitor the home wherever and whenever. From the test results, PIR sensor can detect human movement with a distance of 3.4 meters and the angle is 90o. The Temperature sensors and flame detectors detect temperatures and hotspots with a maximum distance of 25 cm, respectively